PENGARUH PELATIHAN, MOTIVASI KERJA DAN PROMOSI JABATAN TERHADAP KINERJA KARYAWAN CV JAYA BERSAMA CABANG PURWOKERTO - Angga Bayu Dofiansyah; Dyah Supriatin (Jurnal Psikotes, 2026)
This research is motivated by the problem of lack of training for employees causing no development, and lack of work motivation because the company does not give appreciation to employees, as well as job promotions that are less objective to employees. This study aims to analyze the effect of training, work motivation, and job promotions on employee performance at CV Jaya Bersama Purwokerto branch. The research method used is a quantitative method. The population of this study was all employees of CV Jaya Bersama Purwokerto branch, totaling 34 people using saturated samples. The results of the study indicate that the training variable has a positive and significant effect on employee performance. Work motivation also has a positive and significant effect on performance, Job promotions are proven to have a positive and significant effect on employee performance. The coefficient of determination of 0.051 means that this research variable has a 51% effect on employee performance and the remaining 49% is influenced by other factors not examined in this study. The conclusion of this study is that the Influence of Training, Work Motivation, and Job Promotion is an important factor in improving employee performance at CV Jaya Bersama Purwokerto branch.